Peranan Board Size dalam Pengaruh Kontrol Keluarga terhadap Keputusan Membayar Dividen - Nunik Dwi Kusumawati; Edita Rachma Kamila (Nomicpedia: Journal of Economics and Business Innovation, 2023)
This study aims to determine the effect of family control on the dividend-paying decisions. The sampling method used purposive sampling, and the analytical method used in this study was the logistic regression method. Based on the results of the analysis it can be concluded that family control has a significant negative effect on the decision to pay dividends. This study also looks at the role of board size in moderating the effect of family control on dividend-paying decisions. The board size variable does not moderate the effect of family control on the decision to pay dividends. It only acts as a predictor variable, where board size has a positive effect on the dividend-paying decisions.